Stone cobra: "Adult" left single system ureterocele with 139 calculi-case report and review of the literature - Ogwuche Ei; Ojo Ba; Efu Me (Archive of Urological Research - Peertechz Publications, 2020)
A 35yr old man old with no previous major clinical issues presented with a 2years history of radiating left flank pain and dysuria. Abdominopelvic ultrasonography and an intravenous urography confirmed a bladder stone and a left single unit ureterocele harboring multiple stones showing as a typical "Cobra head" with resultant hydronephrosis. A cystolithotomy and incision with marsurpialization of the orthotopic ureterocele with extraction of 139 calculi was done. The post operative recovery was uneventful with resolution of his symptoms. Follow up ultrasonography at three and six months show resolved hydronephrosis with no residual stones seen. Adult orthotopic ureterocele even in the presence of multiple stones has a good outcome after open surgery.